Augmentation mammoplasty and mastopexy with somersault flap from reverse abdominoplasty - Giovanna Calil Vicente Franco de Souza; Claudio Messias Moraes; Diogo Nascimento dias De Aguiar; Rodrigo Bagattini Cruz; Leandro Tuzuki Cavalheiro; Ricardo Portella Perrone (Revista Brasileira de Cirurgia Plástica, 2020)
Introduction: The breasts and abdomen undergo significant morphological changes with massive weight loss. Breast augmentation is one of the most commonly performed procedures in plastic surgery, unlike reverse abdominoplasty, which has been little described. However, in patients with upper abdominal flaccidity who want breast augmentation, breast augmentation through reverse abdominoplasty (AMBRA) makes it possible to improve the breasts and abdominal contour simultaneously. This work aims to describe a case of breast augmentation and mastopexy using a somersault flap from reverse abdominoplasty. Case Report: Female patient, brown, with a history of massive weight loss and previous mammoplasty and abdominoplasty, evolved with breast ptosis and lipodystrophy in the upper abdomen. She underwent reverse abdominoplasty using an epigastric dermofat flap for breast projection. The patient had a good postoperative evolution, with satisfactory surgical results. Discussion: Massive weight loss can result in deformities in the breasts and abdomen that require reparative surgery. Breast remodeling is arduous and may require the use of adjacent tissues. Abdominoplasty, in turn, is the most established technique for rejuvenating the trunk; however, when sagging mainly affects the upper abdomen, reverse abdominoplasty becomes an option. In cases where the desire for breast augmentation is associated with excess supraumbilical volume, AMBRA should be considered. Breast augmentation using reverse abdominoplasty proved to be a viable technique in this case, with a satisfactory final result.